Stake effects on ambiguity attitudes for gains and losses - Ranoua Bouchouicha; Peter Martinsson; Haileselassie Medhin; Ferdinand M. Vieider (Theory and decision: an international journal for multidisciplinary advances in decision science, 2017)
We test the effect of stake size on ambiguity attitudes. Compared to a baseline condition, we find subjects to be more ambiguity seeking for small-probability gains and large-probability losses under high stakes. They are also more ambiguity averse for large-probability gains and small-probability losses. We trace these effects back to stake effects on decisions under risk (known probabilities) and uncertainty (unknown probabilities). For risk, we replicate previous findings. For uncertainty, we find an increase in probabilistic insensitivity under high stakes that is driven by increased uncertainty aversion for large-probability gains and for small-probability losses.
Keywords: 330; Monetary stakes; Ambiguity aversion; Risk attitudes